A Tool: Finding Optimum Base Station Location with S-UTD Model - Aydın, Alp Eren; Tabakcıoğlu, Mehmet Barış (Ieee, 2019)
Placing of a TV broadcasting station to the best convenient location is vital to establish high QoS and reliable TV broadcasting systems. To realize efficient broadcasting system, before deploying the TV station, coverage map of this station have to be predicted. In order to predict the coverage map total electric field have to be calculated by electromagnetic wave propagation models. All the direct and/or diffracted rays emanate from the transmitter reach to receiver have to be determined and total field have to be calculated in all point. Slope diffraction (S-UTD) model is a propagation model and can be used in coverage mapping. In this study, optimum base station location has determined by using randomly distributed 196 obstacles in a region.
PhotonIcs and Electromagnetics Research Symposium - Spring (PIERS-Spring) -- JUN 17-20, 2019 -- Rome, ITALY
Keywords: [No Keywords]